Analisis Kesulitan Penyelesaian Tugas Akhir Skripsi Pada Mahasiswa Jurusan Pendidikan Ekonomi Fakultas Ekonomi dan Bisnis Universitas Negeri Manado - Tessa Gimon; Febriyani Rattu; Listriyanti Palangda (Peneliti.net, 2026)
This study aims to analyze the obstacles faced by students in completing their final thesis assignments at the Department of Economics Education, Faculty of Economics and Business, Manado State University. Writing a thesis is one of the academic requirements that students must fulfill to obtain a bachelor's degree. However, in the process of writing, students often face various obstacles that have the potential to delay their studies. This study was conducted using a descriptive qualitative approach. Informants in this study involved six students from the Economics Education Study Program, consisting of three students from the 2019 intake and three students from the 2020 intake, who were selected using a purposive sampling technique. The following approaches were used to collect information: in-depth interviews, observation, and documentation. The Miles, Huberman, and Saldaña methodology, which consists of three stages: information reduction, information presentation, and formulation and verification of conclusions, was used for information analysis in this research. Source triangulation, technical triangulation, member verification, transferability, and reliability methodology were used to calculate the accuracy of the information. The research findings show that students' primary challenges in completing their theses are related to several aspects, including their inability to master research procedures, select research topics, collect data, process data using statistical software, compile literature reviews, and write scientific papers according to academic standards. Furthermore, time constraints and communication problems with supervisors pose challenges for students throughout the tutorial process. Stress, academic pressure, side jobs, and poor time management are the main reasons why students lack motivation to complete their theses. The research findings also show that support from friends, family, and supervisors is crucial in increasing students' motivation to complete their theses.